Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Pakan Ternak Konsentrat - Rap Sanjani; Halimah Zahrah (Indo Publishing, 2026)
This study aims to analyze the influence of product quality and price on purchasing decisions for concentrate livestock feed at CV Mitra Bumi Berkah. The research background stems from a sales decline anomaly despite the company offering the lowest market price. The methodology employs a quantitative associative approach using purposive sampling with 50 cattle farmers as respondents. Data analysis was conducted via Multiple Linear Regression using SPSS software. Results demonstrate that product quality and price have a positive and significant effect on purchasing decisions, both partially and simultaneously. The coefficient of determination (R2) of 62.4% explains the model's ability to represent the variation in purchasing decisions. Product quality exhibits a more dominant regression coefficient compared to the price variable. These findings imply that farmers are rational actors who prioritize nutritional performance over low prices alone.